Optimal Dextrose Concentration for Pain Control in Healthy Newborns during Hepatitis B Vaccination - Seong Hee Oh; In Ah Kim; Hyunseung Jin (Korean Society of Neonatology, 2018)
Purpose Glucose has been recommended as an analgesic for mild to moderately painful procedures in neonates. The goal of this study was to assess the optimal dextrose concentration for pain control in newborns. Methods This prospective, randomized, blinded clinical trial included 116 healthy full-term newborns. The neonates were randomly assigned to the following four groups by drawing straws: groups receiving sterile water or a 10%, 20%, or 40% dextrose solution orally. Each group was treated with the assigned solution prior to hepatitis B vaccination. The Neonatal Facial Coding System (NFCS) and the Neonatal Infant Pain Scale (NIPS) scores were evaluated before, immediately after, and 2 minutes after the injection in all neonates. Premature Infant Pain Profile (PIPP) scores were evaluated during the injection. All procedures were video-recorded, and pain scores were assessed by two independent observers who were not involved in the care of the newborns studied. The pain scores were compared among the four groups. Results The 40% dextrose solution significantly reduced the NFCS (P=0.002) and the PIPP scores (P=0.001) compared with sterile water. No hyperglycemic events were noted in the study subjects 2 hours after the injection. Conclusion The 40% dextrose solution effectively relieved pain due to intramuscular injection in full-term newborns without causing hyperglycemic events. However, the 10% and 20% dextrose solutions did not affect neonatal pain scores.